Local embeddedness, upgrading, and skill development: Global value chains and foreign direct investment in Lesotho's apparel industry - Cornelia Staritz; Mike Morris (Austrian Foundation for Development Research (ÖFSE), 2012)
Many low-income countries (LICs) are integrated into apparel global value chains (GVCs) through foreign direct investment (FDI). This is also the case in Lesotho that has developed to the largest Sub-Sahara African (SSA) apparel exporter to the US under the African Growth and Opportunity Act (AGOA). More recently, a new apparel export market has emerged in Lesotho the regional market of South Africa. The two export markets US and South Africa are supplied by different types of FDI firms affiliates of largely Taiwanese transnational producers and South African manufacturers that are incorporated into distinct value chains. This paper assesses the implications for upgrading of integration into these two value chains in Lesotho - the value chain characterized by Taiwanese investment and feeding into the US market under AGOA and the value chain characterized by South African investment and feeding into the South African market. These value chains differ with regard to ownership patterns, end markets, export products, governance structures and firm set up, investors motivations, and perceptions on main challenges. These different characteristics have crucial impacts on upgrading possibilities, including functional, process and "local" upgrading. Thus, from the perspective of upgrading and sustainability, ownership patterns, local embeddedness and market diversification matter. The emergence of South Africa as an alternative end market and the different value chain dynamics operating in the South African retailer-governed value chain open up new opportunities from those of the AGOA/Taiwanese-dominated value chain.
Keywords: 330; Auslandsinvestition; Wertschöpfung; Export; Bekleidungsindustrie; Lesotho